Precise antibacterial therapeutics based on stimuli-responsive nanomaterials - Wu, Ziqi; Nie, Ran; Wang, Yao; Wang, Qihui; Li, Xiang; Liu, Yuguang (Frontiers in Bioengineering and Biotechnology, 2023)
Bacterial infection refers to the process in which bacteria invade, grow, reproduce, and interact with the body, ultimately causing a series of pathological changes. Nowadays, bacterial infection remains a significant public health issue, posing a huge threat to human health and a serious financial burden. In the post-antibiotic era, traditional antibiotics are prone to inducing bacterial resistance and difficulty in removing bacterial biofilm. In recent years, antibacterial therapy based on nanomaterials has developed rapidly. Compared with traditional antibiotics, nanomaterials effectively remove bacterial biofilms and rarely result in bacterial resistance. However, due to nanomaterials’ strong permeability and effectiveness, they will easily cause cytotoxicity when they are not controlled. In addition, the antibacterial effect of non-responsive nanomaterials cannot be perfectly exerted since the drug release property or other antibacterial effects of these nano-materials are not be positively correlated with the intensity of bacterial infection. Stimuli-responsive antibacterial nanomaterials are a more advanced and intelligent class of nano drugs, which are controlled by exogenous stimuli and microenvironmental stimuli to change the dosage and intensity of treatment. The excellent spatiotemporal controllability enables stimuli-responsive nanomaterials to treat bacterial infections precisely. In this review, we first elaborate on the design principles of various stimuli-responsive antibacterial nanomaterials. Then, we analyze and summarizes the antibacterial properties, advantages and shortcomings of different applied anti-bacterial strategies based on stimuli-responsive nanomaterials. Finally, we propose the challenges of employing stimuli-responsive nanomaterials and corresponding potential solutions.